Exploring the Association of Innate Immunity Biomarkers With MRI Features in Both Early and Late Stages Osteoarthritis - Rajandran, Sureka Naidu; Ma, Cheryl Ann; Tan, Jin Rong; Liu, Jin; Wong, Steven Bak Siew; Leung, Ying-Ying (Frontiers in Medicine, 2020)
Objective. To evaluate the association between biomarkers of innate immunity and the magnetic resonance imaging (MRI) features of earlier and later stages of KOA. Methods. From 139 and 20 participants with earlier and later stages of KOA, we analysed knee MRIs scored using the Boston Leeds Osteoarthritis Knee Score (BLOKS) at recruitment with biomarkers. In paired serum (s) and synovial fluid (sf), we quantified three biomarkers related to innate immunity: Lipopolysaccharide Binding Protein (LBP), CD14 and toll-like receptor 4 (TLR4); and three pro-inflammatory biomarkers (IL6, IL8 and TNFα). Results. In participants with earlier KOA, (s) LBP was statistically significantly associated with meniscal extrusion and (sf) CD14 was associated with effusion after adjustment with age, gender and body mass index. In participants with later stage of KOA, (sf) LBP was associated with effusion. (sf) CD14 was associated with cartilage loss and BML. In earlier stage of KOA, the pro-inflammatory biomarkers IL6, IL8 and TNFα were associated with most MRI features. Conclusion. Innate immunity biomarkers (s) LBP was associated with MRI meniscal extrusion, (sf) CD14 was associated with MRI synovial inflammation in earlier stage; and BMLs in later stage of KOA. Associations between pro-inflammatory biomarkers and varies MRI features in earlier stage of KOA was observed.